EEMCO guidance to the in vivo assessment of tensile functional properties of the skin - Part 2 - Rodrigues, L (2015)
Tensile functions of the skin and subcutaneous tissues contribute to the appearance of the aged and photodamaged skin and to the effects of various other pathophysiological processes. The assessment of tensile functions of skin can be performed by distinct approaches mainly characterized by the orientation and magnitude of the imposed stress and strain overtime. Testing methods are basically grouped into five major classes which include tensile, torsional, indentation, impact and elevation modes. Computed tensile variables are reproducible when the experimental procedure occurs under fully controlled conditions. Consistent and relevant information is yielded when the limitations and pitfalls typical for each test method are taken into consideration. Copyright (C) 2001 S. Karger AG, Basel.